(untitled) (KYAMC Journal, 2025)
Background: Antimicrobial resistance (AMR) in intensive care units (ICUs) cause significant mortality, particularly in resource-limited settings. The traditional antibiotics become ineffective in our hospital settings. Objectives: This study aimed to evaluate the current trends of antibiotic resistance patterns among adult patients in ICU settings of a peripheral hospital in Bangladesh. Materials and Methods: A cross-sectional study was conducted between January 2023 to December 2023, analyzing bacterial isolates from adult ICU patients. Samples were collected from blood, urine, respiratory secretions, and wound swabs. Identification of bacteria and antimicrobial susceptibility testing were performed using automated BD Phoenix™ M50 System and manual (disc diffusion) methods. Data analysis was conducted using SPSS version 25. Results: Among 100 patients studied (65% male, mean age 51.70 ±17.96 years), blood was the majority of specimens (40%). Escherichia coli was the most frequently isolated organism (31%), followed by Staphylococcus species (27%). E. coli demonstrated resistance to 15 out of 16 tested antibiotics, while Klebsiella pneumoniae and Staphylococcus aureus showed resistance to 12 antibiotics each. The highest resistance rates were observed to clindamycin (76.09%), ceftazidime (70.83%), and colistin (70.27%), while amikacin showed the lowest resistance rate (29.87%). Conclusions: The study revealed alarming levels of antimicrobial resistance among ICU isolates, particularly concerning the high resistance to colistin. These findings emphasize the urgent need for robust antibiotic stewardship programs and enhanced infection control measures in ICU settings of peripheral hospitals in Bangladesh. KYAMC Journal Vol. 16, No. 01, April 2025: 9-13